2011
DOI: 10.1615/jenvironpatholtoxicoloncol.v30.i1.50
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory influence of Phyllanthus niruri on oxidative stress, antioxidant defense and chemically induced skin tumors

Abstract: The present study evaluates the modulatory potential of Phyllanthus niruri on chemically induced skin carcinogenesis, and its influence on oxidative stress and the antioxidant defense system. Oral administration of P. niruri extract (PNE), during peri- (Gr. III), post- (Gr. IV), or peri- and post- (Gr. V) initiational stages of 7,12-dimethylbenz(a) anthracene (DMBA)-croton oil–induced papillomagenesis considerably reduced tumor burden to 4.20, 4.00, and 3.33(positive control value 6.20); cumulative number of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Recently, hepatoprotective (Ho et al, 2012), antipyretic, anti-inflammatory, antinociceptive (Obidike et al, 2010), antiplasmodial (Mustofa et al, 2007), and antitumor activities by enhancing antioxidant defense (Sharma et al, 2011) have been reported for Phyllanthus niruri L. (Chancapiedra). In a screening test for the detection of plants with anti-H. pylori activity, P. niruri showed anti-H. pylori effects against metronidazole-resistant H. pylori strains (Uyub et al, 2010).…”
Section: Phyllanthus Nirurimentioning
confidence: 99%
“…Recently, hepatoprotective (Ho et al, 2012), antipyretic, anti-inflammatory, antinociceptive (Obidike et al, 2010), antiplasmodial (Mustofa et al, 2007), and antitumor activities by enhancing antioxidant defense (Sharma et al, 2011) have been reported for Phyllanthus niruri L. (Chancapiedra). In a screening test for the detection of plants with anti-H. pylori activity, P. niruri showed anti-H. pylori effects against metronidazole-resistant H. pylori strains (Uyub et al, 2010).…”
Section: Phyllanthus Nirurimentioning
confidence: 99%
“…P. niruri has been found to exhibit antitumor [ 8 ], antiviral [ 4 ], antioxidant [ 9 ], anti-inflammatory [ 10 ], and antidiabetic [ 11 ] activities and radiation protection [ 12 ]. Particularly in antitumor activity, P. niruri extract shows potential in reducing chemically induced skin papillomas by enhancing antioxidant defense systems [ 13 ] and shows potential in the management of a two-stage skin carcinogenesis model in mice. The methanol extracts of P. niruri exhibited a 59.5% inhibition of rat aortic vascular growth and showed a significant decrease of 37.9% in the tube formation assay involving human umbilical vein endothelial cells (HUVECs) on Matrigel [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these, the development of novel anticancer agents is an immense demand. Previous reports had implied that P. niruri is a candidate folk medicine [ 13 , 18 , 19 ]. However, most of previous studies in vitro/vivo just focused on the crude extracts from P. niruri [ 3 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…DC. and M. pulegium aqueous and ethanolic extracts, have been shown to have several pharmacological properties [12][13][14][15][16][17][18][19][20][21][22] . Nevertheless, few studies have evaluated the effects of aqueous extracts, prepared as a tea, from these plants.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, aqueous herbal extracts have attracted attention since they can be consumed in a daily basis as infusions. Additionally, the mechanism(s) involved in those therapeutic properties [12][13][14][15][16][17][18][19][20][21][22] , especially on antioxidant effect from these plants, are not fully understood. Of particular importance, it could be emphasized that supporting scientific data, concerning the neuroprotective potential of these plants, especially from aqueous extracts, are still scarce.…”
Section: Introductionmentioning
confidence: 99%